27‐2: Invited Paper: Soluble Small Molecules in Top Emission OLED Devices from Ink Jet Printing: Requirements and Performance Status. Issue 1 (25th September 2020) - Meyer, Sebastian; Stolz, Sebastian; Hamburger, Manuel; Tseng, Hsin-Rong; Engel, Miriam; Hayer, Anna; Linge, Rouven; Tierney, Steven; Bernatz, Georg; Anémian, Rémi
Abstract : Inkjet printing (IJP) is on the rise to become a competitive production technology for organic light emitting diodes (OLEDs). Recent progress in printing technology with drop volumes down to the pL regime as well as constant performance improvements from material point of view have opened the way towards IT displays. Here target resolutions are 250 ppi and beyond. For this purpose, small molecules are highly suitable due to their low impact on ink viscosity and excellent device performance. Their current performance status is reviewed based on bottom and top emission. For the latter, crucial factors for high performance like film uniformity and precise thickness control are discussed.